Distribution of parasitic diseases in children by age and gender (Eurasian Research Bulletin, 2023)
Helminthiasis is a widespread infectious disease among children and poses a serious threat to children's health. According to the World Health Organization (WHO), parasitic diseases are the third most common infectious disease after coronary heart disease (after diarrhea and tuberculosis). To date, about 350 species of helminths have been proven to be parasitic in the human body. According to many authors, more than 40 species of parasites are carcinogenic to humans and animals. Helminthoses are chronic parasitic diseases in which all organs and systems are involved in the process. In total, there are more than 250 species of helminths, and about 90 species are found in the CIS countries. In the years of independence, the processes of improving health care in the Republic of Uzbekistan rose to the level of state policy. Nevertheless, there are a number of problems in the field of health care. Among them, one of the important problems is the spread of parasitological diseases among the population, the lack of optimal methods of their early diagnosis and treatment